PARADOX OF CONSUMPTION IN ISLAMIC ECONOMICS: BETWEEN ANTI-ISRAF PRINCIPLE AND FINANCIAL POLICIES - Insyirahti Salsabilla, Dewi; Fakhrina, Agus (Journal of Religious Policy, 2025)
Islamic economic principles emphasize the prohibition of israf (excessive consumption) as a fundamental ethical guideline in financial management. However, government economic policies that promote expanded access to financing may create tensions with this principle. This study examines the alignment between the anti-israf principle in Islamic finance and several government economic policies, namely the Financial System Stability (SSK) Regulation No. 2/KSSK/Pers/2025, the Regulation of the Minister of Public Works and Public Housing of the Republic of Indonesia No. 35 of 2021 concerning Housing Financing Facilities and Assistance for Low-Income Communities, and the regulation of Buy Now Pay Later (BNPL) schemes. This research employs a literature review method with a normative-critical approach to assess the consistency of financing policies with Islamic ethical principles, particularly within Indonesia’s dual banking system. The findings indicate that policy orientations toward increasing consumer financing have not been adequately accompanied by mechanisms that encourage prudent financial behavior. In the absence of sufficient financial literacy, such policies risk fostering consumptive behavior that contradicts the anti-israf principle in Islamic finance. Therefore, the study argues for the integration of financing regulations with value-based financial literacy rooted in Islamic ethics, so that economic policies not only support financial system stability and economic growth but also uphold moderation and justice as core values of Islamic economics.